Strategies to Prevent or Remediate Cancer and Treatment-Related Aging. (29th April 2020) - Guida, Jennifer L; Agurs-Collins, Tanya; Ahles, Tim A; Campisi, Judith; Dale, William; Demark-Wahnefried, Wendy; Dietrich, Jorg; Fuldner, Rebecca; Gallicchio, Lisa; Green, Paige A; Hurria, Arti; Janelsins, Michelle C; et al.
Abstract: Up to 85% of adult cancer survivors and 99% of adult survivors of childhood cancer live with an accumulation of chronic conditions, frailty, and/or cognitive impairments resulting from cancer and its treatment. Thus, survivors often show an accelerated development of multiple geriatric syndromes and need therapeutic interventions. To advance progress in this area, the National Cancer Institute convened the second of 2 think tanks under the auspices of the Cancer and Accelerated Aging: Advancing Research for Healthy Survivors initiative. Experts assembled to share evidence of promising strategies to prevent, slow, or reverse the aging consequences of cancer and its treatment. The meeting identified research and resource needs, including geroscience-guided clinical trials; comprehensive assessments of functional, cognitive, and psychosocial vulnerabilities to assess and predict age-related outcomes; preclinical and clinical research to determine the optimal dosing for behavioral (eg, diet, exercise) and pharmacologic (eg, senolytic) therapies; health-care delivery research to evaluate the efficacy of integrated cancer care delivery models; optimization of intervention implementation, delivery, and uptake; and patient and provider education on cancer and treatment-related late and long-term adverse effects. Addressing these needs will expand knowledge of aging-related consequences of cancer and cancer treatment and inform strategies to promote healthy aging of cancer survivors.